Discovering statistics using IBM SPSS statistics and sex and drugs and rock 'n' roll - Field, Andy P. (SAGE, 2013)
Unrivalled in the way it makes the teaching of statistics compelling and accessible to even the most anxious of students, the only statistics textbook you and your students will ever need just got better! Andy Field's comprehensive and bestselling Discovering Statistics Using SPSS 4th Edition takes students from introductory statistical concepts through very advanced concepts, incorporating SPSS throughout.